IMPLEMENTING COOPERATIVE GAME-BASED LEARNING TO ENHANCE STUDENTS’ MOTIVATION IN ENGLISH LEARNING - Faiqohan Salsabila Huwaidah; Gusti Nur Hafifah; Nur Afifah (PROCEEDING UMSURABAYA, 2026)
This classroom action research explores the effectiveness of integrating game-based cooperative learning to enhance student motivation in English language learning at SMP Negeri 4 Surabaya, Class VII-F. Sparked by declining engagement due to monotonous teaching methods, the study adopts Kurt Lewin’s action research model, implemented in one cycle. Thirty-three students participated, with data gathered through observation sheets and Likert-scale questionnaires, targeting six motivational indicators: interest, active participation, task consistency, self-confidence, questioning initiative, and teamwork. The findings reveal a significant improvement across all indicators following the implementation of educational games such as Vocabulary Match!, Reading Race, and Descripto Dash!. Students became more enthusiastic, cooperative, and confident—particularly when given positive reinforcement and grouped heterogeneously. Questionnaire results reinforced these observations, with students responding positively to the playful yet purposeful learning design. The study concludes that game-based cooperative learning offers a powerful, student-centered strategy to transform classroom dynamics and spark motivation in learning English, especially for descriptive text comprehension.